Argonne Mine, loading blast holes - Anderson, F. G.; Arthur Lakes Library; Russell L. and Lyn Wood Mining History Archive; United States. Bureau of Mines (Colorado School of Mines. Arthur Lakes Library, 1947)
Date scanned: 2002-6-12. H-7; Loading blast holes. Note blast hole full of water to collar as stemming is being shoveled into hole. Bell guide chained to drill mast, hood for protection of driller. Argonne Mine, The M. A. Hanna Company, Keewatin, Minnesota. - F. G. Anderson - July 24, 1947. Held in the Russell L. and Lyn Wood Mining History Archive, Arthur Lakes Library, Colorado School of Mines. Donor: United States Bureau of Mines. A miner loads blast holes at the Argonne Mine. The Argonne open pit iron mine in the Mesabi Range in Itasca County, Minnesota was operated by the M. A. Hanna Company. The M. A. Hanna Company was one of the large mining companies that moved into the iron areas of the Lake Superior region in the early 1900s, consolidating smaller properties and engaging in exploration for other economic deposits. The Company was dissolved in 1965, then resurrected in 1985.